Oxidative Transformation of Ethylbenzene Utilizing Metal Bound Immobilized Catalysts - Kumari, S.; Gupta, P.K.; Kumar, A.; Kumar, R. (Eurasian Journal of Chemistry, 2025)
In the present contribution, we have investigated the catalytic potential of immobilized metal catalysts for the oxidation of ethylbenzene. Chloromethylated polystyrene was initially converted to aldehydopolystyrene followed by its functionalization with 2-aminothiophenol to get functionalized resin. This resin was successfully binded with appropriate metal (Mn(II), Fe(III), Ni(II), Cu(II), VO(II)) salts to prepare different heterogeneous catalysts which were characterized using CHNS, energy dispersive X-ray spectroscopy (EDX), diffuse reflectance spectra (DRS), fourier transform infrared spectra (FTIR), atomic absorption spectrophotometry (AAS) and electron paramagnetic resonance (EPR) spectra techniques. Metal binding in mmol per gram of resin fordifferent catalysts was found in the range 0.96–1.24. The catalytic potential of these supported catalysts was assessed for the oxidation of ethylbenzene, utilizing hydrogen peroxide (H2O2) and tert-butyl hydroperoxide (TBHP) as the oxidants. The effects of various reaction parameters, such as temperature, reaction duration, type of oxidant, and the amount of catalyst used were examined for the oxidation reaction. Under optimized milder conditions, the results showed that H2O2 as oxidants resulted in 53.8 % conversion rates with the copper catalyst. The nickel catalyst, when used with H2O2, showed the highest selectivity for acetophenone, reaching 83 %. The recovered catalysts retained its original structure, as established by a comparative analysis of DRS and FT-IR spectra of both the original and reused catalysts. Moreover, the catalysts can be employed repeatedly up to five times under optimum conditions without any noticeable reduction in activity.
Keywords: immobilization; catalyst; nickel; copper; recycle; oxidation; ethylbenzene; polymer